Cold pressed avocado oil : impact of adding skin and seed during malaxing : a thesis submitted in fulfilment of the requirements for the degree of Master of Food Technology at Massey University, New Zealand - Liang, Yutong (Massey University, 2024)
The production of extra virgin cold-pressed avocado oil is based on the mechanical extraction of olive oil, involving grinding, malaxing and centrifugation, which mainly extracted oil from the mesocarp of avocado fruit. During processing a step in the process is included to eliminate skin and seed before extraction. The aim of this study was to determine the effect of incorporating avocado skin and seed during the cold press extraction process on oil yield, oil composition and oil storage stability. Laboratory-scale extraction equipment was used to extract oil from ‘Hass’ avocados, harvested in July 2022 (late season fruits from the previous season) and in August 2022 (early season fruits for the new season). Three different tissue combinations in the malaxers were investigated: flesh with 10% of the skin tissue, flesh with 100% skin, flesh with 100% skin and seed (whole fruit). Each oil was immediately transferred into amber bottles, nitrogen flushed the headspace and then stored at 20℃, 30℃ and 40℃ for the storage trial. Oil samples were also stored at -20C to be used for analysis of composition. The oil yield (kg oil/ (kg of wet tissue in malaxer)) from malaxing whole fruit was considerably less than from malaxing flesh with 10% skin; 65% and 35% less for early and late season, respectively. Adding skin and seed did not significantly change the free fatty acid and peroxide value in oil, although the UV absorbance values (K232 and K270) were higher in whole fruit oil. While there were no significant differences in fatty acid and sterol profiles, the whole fruit oil contained significantly higher concentrations of phenolics, sterols and pigments (carotenoids and chlorophylls) (p < 0.05). During storage, oils at higher storage temperatures exhibited a more rapid increase in peroxide value (PV) and K values, along with a more rapid decline in total phenolics and total chlorophyll. Informal sensory trials suggested that the bitterness of the oil increased with storage time, though sensory was not evaluated. It can be concluded that the addition of skin and seed led to a reduction in oil yield due to the lower proportion of flesh mass in malaxer, however more liposoluble compounds dissolved in the oil. Although the Rancimat test indicated improved oxidative stability with the addition of skin and seed, the whole fruit oil demonstrated a higher oxidation rate during storage, coupled with increased sensitivity to temperature.
Figures are reproduced with permission.
Keywords: extra virgin avocado oil; cold-pressed; skin; seed; composition; stability; 300607 Food technology